[quotation] On things we shall miss in 2020 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On things we shall miss in 2020: 'I think what people in the ACP will miss most will be the almost complete collapse of the extended family system where everybody is their brother s keeper. This will be replaced when rigorous capitalism comes into...